Differences in the ichthyofauna feeding habits among lateral lagoons and the river channel in a large reservoir - Ferrareze, Mateus [UNESP]; Nogueira, Marcos Gomes [UNESP]; Casatti, Lilian [UNESP] (FapUNIFESP (SciELO), 2015)
In this study, we investigated differences in feeding habits of small-sized ichthyofauna among lateral lagoons and the river channel in a large reservoir. The study was performed in four lagoons and in one sampling site of the main channel in Rosana Reservoir, Paranapanema River, Brazil. The samples were taken in September and November of 2004 and in January, March, May, and August of 2005. Fish were sampled with a 7.5 m2 hand net. Five manual throws were made toward aquatic macrophytes stands. The sampling design favored the collection of small-sized fish fauna (juveniles/small-sized species). The stomach contents of 42 species were analyzed. A total of 183 different items were consumed by fish. These items were grouped in 11 food categories, which were used to classify fish into seven trophic guilds. Aquatic insects were consumed by 32 species and were the predominant feeding item. In the river, the most consumed items were aquatic insects, cladocerans, and phytoplankton, whereas in the lagoons aquatic insects, copepods, and cladocerans were the main items. By comparing each trophic guild, the number of insectivores, algivores, and zooplanktivores species was higher in the lagoons than in the river, and the opposite was found only for omnivore fish. Low niche width in all sites indicates high trophic specialization and low niche overlap between pairs of species. Fish assemblage in the lateral lagoons presents feeding habits distinct from those of the river species, indicating that the coexistence and high abundance of small-sized fish in the sampling sites are explained by their high feeding adaptability, which includes a tendency toward dietary specialization, low feeding overlap, and resource partitioning, along with different temporal resource uses.

O objetivo deste estudo foi avaliar a diferença no hábito alimentar da ictiofauna entre lagoas laterais e o canal do rio num reservatório de grande porte. O estudo foi realizado em quatro lagoas e um ponto no reservatório de Rosana, rio Paranapanema, Brasil. As amostras foram coletadas em setembro e novembro de 2004 e janeiro, março, maio e agosto de 2005. Foram realizados cinco arrastos manuais com uma rede de 7,5m2 , junto aos bancos de macrófitas aquáticas. O desenho amostral favoreceu a coleta de peixes juvenis e espécies de pequeno porte. Os conteúdos estomacais de 42 espécies foram analisados. Um total de 183 diferentes itens foi consumido, que foram agrupados em 11 categorias alimentares. Sete guildas tróficas foram estabelecidas. Insetos aquáticos foram consumidos por 32 espécies de peixes, sendo o item alimentar predominante. O padrão alimentar da ictiofauna no rio foi diferente quando comparado as lagoas, como demonstrado na Análise de Correspondência Destendenciada. No rio, os principais itens alimentares foram insetos aquáticos, cladóceros e fitoplâncton, enquanto que nas lagoas os principais itens foram insetos aquáticos, copépodes e cladóceros. Comparando-se cada guilda trófica, o número de espécies de insetívoros, algívoros e zooplanctívoros foi maior nas lagoas do que no rio e o oposto foi encontrado somente para os onívoros. Foram registrados baixos valores de amplitude de nicho, indicando que as espécies apresentam alta especialização trófica, e baixa sobreposição de nicho trófico entre os pares de espécies. Finalmente, este estudo mostra que a coexistência e alta abundância das espécies de peixe de pequeno porte encontrada nas lagoas laterais são explicadas pela adaptabilidade alimentar, o uso temporal dos recursos pelos peixes e pela ampla disponibilidade de alimento existente nas lagoas.
As diferenças nos hábitos alimentares da ictiofauna entre lagoas laterais e o canal do rio em um grande reservatório
Keywords: Paranapanema river; Small fish; Trophic guilds; Diet; Feeding pattern; Rio Paranapanema; Peixes de pequeno porte; Guildas tróficas; Dieta; Padrão alimentar